Prevalence of colistin resistance gene mcr-1 in Escherichia coli isolated from chickens in central China, 2014 to 2019. (June 2022) - Zhang, Wenting; Zhang, Tengfei; Wang, Chen; Liang, Guixing; Lu, Qin; Wen, Guoyuan; Guo, Yunqing; Cheng, Yiluo; Wang, Zui; Shao, Huabin; Luo, Qingping
Highlights: This study investigated the prevalence of chicken mcr-1- harbouring Escherichia coli isolated from 16 different cities in central China from 2014 to 2019. The mcr-1 positive rate varied enormously during 2014–2019 in central China. The ban on colistin likely decreased the dissemination of mcr-1 on chicken E. coli isolates. Multidrug-resistant trait is observed in mcr-1 positive E. coli isolates and can be transferred into other transconjugants. ABSTRACT: Objectives: This study investigated the prevalence and characteristics of mcr-1- harbouring Escherichia coli isolated from chickens in central China from 2014 to 2019. Methods: A total of 1132 E. coli isolated from 1647 chicken swabs were analysed for colistin susceptibility by broth microdilution method and prevalence of mcr-1 gene by PCR. The colistin-resistant E. coli isolates were typed by multi-locus sequence typing (MLST) and tested with 12 antimicrobial agents. The transconjugation assay was conducted for the mcr-1 -positive isolates using the transconjugant E. coli C600. Results: Of the 1132 E. coli isolated from chickens, 131 isolates (11.6%) exhibited colistin resistance, and 51 isolates (4.5%) were mcr-1 positive. The mcr-1 -positive rate was quite low in 2014 (2.3%) and 2015 (1.7%), increased to peak in 2016 (12.6%) and 2017 (11.4%), and then decreased significantly in 2018 (1.7%) and 2019 (0.9%). The 131 colistin resistant isolates were assigned to 66 unique sequence types (STs), 27 of which contained mcr-1 -positive isolates. Compared with mcr-1 -negative E. coli, mcr-1 -positive E. coli showed higher resistance rates to nalidixic acid, ciprofloxacin, ceftriaxone, cefotaxime, and tetracycline. Furthermore, 30 of the 51 mcr-1 positive isolates transduced their mcr-1 gene into E. coli C600, and 13 of the 30 transconjugants carried more than one replicon types. Conclusion: The mcr-1 positive rate varied enormously during 2014–2019 in central China. The ban on colistin likely decreased the dissemination of mcr-1 in E. coli isolates from chickens. Multidrug-resistant trait is observed in mcr-1 positive E. coli isolates and can be transferred into other transconjugants.